2019
DOI: 10.1038/s41390-019-0508-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and the developing brain: the road to optimizing early neurodevelopment: a systematic review

Abstract: BACKGROUND: Neonatal intensive care practices have resulted in marked improvements in the survival of premature infants; however, they remain at significant risk for adverse neurodevelopmental outcomes. The impact of current nutritional practices on brain development following early extra-uterine exposure in premature infants is not well known. METHODS: We performed a systematic review to investigate nutritional effects on postnatal brain development in healthy term and prematurely born infants utilizing advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 39 publications
0
43
0
4
Order By: Relevance
“…Full fortifier or preterm formula was not started during the 4 weeks after birth for 35% of babies (sites 1-8: 92%; 20%; 47%; 13%; 8%; 14%; 13%, and 30%). The median (IQR) age at achievement of full enteral feeds was 14 (11,17) days and this differed by site (Figure 2C). Of the included babies, 49% (n = 212) were boys, 11% (n = 48) were SGA and 22% (n = 94) were twins (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full fortifier or preterm formula was not started during the 4 weeks after birth for 35% of babies (sites 1-8: 92%; 20%; 47%; 13%; 8%; 14%; 13%, and 30%). The median (IQR) age at achievement of full enteral feeds was 14 (11,17) days and this differed by site (Figure 2C). Of the included babies, 49% (n = 212) were boys, 11% (n = 48) were SGA and 22% (n = 94) were twins (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Full fortifier or preterm formula was not started during the 4 weeks after birth for 35% of babies (sites 1-8: 92%; 20%; 47%; 13%; 8%; 14%; 13%, and 30%). The median (IQR) age at achievement of full enteral feeds was 14 (11,17) days and this differed by site (Figure 2C). From birth to 36 weeks' CA, the median (IQR) change in z-score for weight was −0.48 (−1.09, 0.05), for length −1.16 (−1.86, −0.43), and for head circumference −0.82 (−1.51, −0.19) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatal growth is positively associated with different measures of brain development, including cortical maturation [1], linear measures of brain size [2], brain volumes [3], and neurodevelopmental outcome (NDO) [4][5][6]. Additionally, a recent systematic review showed that nutritional intake is independently associated with brain development [7]. Early cumulative fat and energy intakes were associated with larger brain volumes, improved white matter integrity [3,8], and lower brain injury scores [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is increasing evidence that neurodevelopmental outcomes in very preterm infants are enhanced with increased early postnatal and cumulative energy intake over the duration of hospitalization, as well as more enteral feeding, especially of mother's milk, which is relatively rich in lipid composition. 4,5 It is encouraging, therefore, that in this volume of The Journal, Alburaki et al 6 report more positive head circumference growth in preterm infants from a randomized, nonblinded study in which an intervention group of very preterm infants (n = 45, 27.1 weeks mean gestational age) received earlier and higher dosing of intravenous soy-based lipid emulsion (2 g/kg on day 1, then 3 g/kg/day while receiving intravenous feeding) while a control group (n = 38, 27.3 weeks mean gestational age) received 0.5-1.0 g/kg on day 1, advancing to 3 g/kg/day by daily increments of 0.5-1.0 g/kg. The intervention group by design had higher cumulative lipid intake in the first 7 days after birth (+24%, 13.5 AE 4.2 vs 10.9 AE 3.5 g/kg per day, P = .03).…”
mentioning
confidence: 99%